Determination of aliphatic hydrocarbons in urban runoff samples from the ‘‘Le Marais’’ experimental catchment in Paris centre - Moilleron, R.; Gonzalez, A.; Chebbo, G.; Thevenot, D.R. (Water Research, 2002)
Aliphatic hydrocarbons were assessed in runoff and waste waters from an urban catchment located in Paris. Runoff were sampled from different types of urban surfaces (11 roofs representing four different covering materials, two courtyards and six streets). Waste water samples were collected at the catchment outlet during dry and wet weather periods as well. This paper gives an overview of the results on the concentration and distribution points of view for both the particulate and the dissolved phases. Results were discussed on the basis of the median. Accordingly, the temporal variability was taken into account. Thus, the concentration medians ranged from 345 to 827, from 297 to 790, and from 393 to 1359 mug L-1 in the roof, courtyard and street samples, respectively. The levels found at the catchment outlet during dry and wet weather periods were of the same order of magnitude, i.e. 700 muL(-1). The particulate phase represented 85% of the total aliphatic hydrocarbon content whatever the sample. (C) 2002 Elsevier Science Ltd. All rights reserved.